Residues 315 and 369 in HN Protein Contribute to the Thermostability of Newcastle Disease Virus - Ruan, Baoyang (Front Microbiol, 2020)
Thermostable Newcastle disease virus (NDV) vaccines have been widely used in areas where a “cold-chain” is not reliable. However, the molecular mechanism of NDV thermostability remains poorly understood. In this work, we constructed chimeric viruses by exchanging viral fusion (F) and/or hemagglutinin-neuraminidase (HN) genes between the heat-resistant strain HR09 and thermolabile strain La Sota utilizing a reverse genetic system. The results showed that only chimeras with HN derived from the thermostable virus exhibited a thermostable phenotype at 56°C. The hemagglutinin (HA) and neuraminidase (NA) activities of chimeras with HN derived from the HR09 strain were more thermostable than those containing HN from the La Sota strain. Then, we used molecular dynamics simulation at different temperatures (310 K and 330 K) to measure the HN protein of the La Sota strain. The conformation of an amino acid region (residues 315–375) was observed to fluctuate. Sequence alignment of the HN protein revealed that residues 315, 329, and 369 in the La Sota strain and thermostable strains differed. Whether the three amino acid substitutions affected viral thermostability was investigated. Three mutant viruses based on the thermolabile strain were generated by substituting one, two or three amino acids at positions 315, 369, and 329 in the HN protein. In comparison with the parental virus, the mutant viruses containing mutations S315P and I369V possessed higher thermostablity and HA titers, NA and fusion activities. Taken together, these data indicate that the HN gene of NDV is a major determinant of thermostability, and residues 315 and 369 have important effects on viral thermostability.